“Al-Jamaal” as a concept of Islamic aesthetics: from the perspectives of religion and art - Che Man, Shaibatul’Islamiah; Mansor, Mazlina; Zakariya, Khalilah; Zen, Ismawi (American Scientific Publishers, 2016)
The concept of aesthetics has received a growing attention from Western scholars since the nineteenth century. Over the past centuries until today, there has been substantial research by Western scholars on various arts produced by the Muslims. However, the concept of aesthetics has captured the special attention of researchers from different fields during the past three decades. The meanings of aesthetics in Islam has long been exposed to the approach that integrates to the understanding of the opposed Islamic worldviews. In fact, many scholars attempt to incapacitate the meaning of Islamic aesthetic merely form tangible forms rather than its contents. Thus, this paper aims to explore and discuss “Al-Jamaal” an Arabic term that means “beauty” as an Islamic aesthetic concept that offers preliminary guidelines in defining Islamic aesthetics, particularly in built environment context. The two objectives of this paper are (1) To explore the meanings of aesthetics in accordance Al- Jamaal concept based on literature review, and (2) To discuss the meanings of “Al-Jamaal” concept from the perspectives of religion and art. The study is conducted through a systematic literature review on Al-Jamaal based on the Quranic perspectives and prophetic traditions, and conducting in-depth interviews with 15 key informants with religious and arts background. Based on the findings, this study establishes nine parameters of the Al-Jamaal concept of Islamic aesthetics, which are spiritual, application, the manner of execution, sense of belonging, ethics, linguistic, self-experience, knowledge and personal expression. This study concludes that “Al-Jamaal” represents a broader meanings of aesthetics in Islam